2016
DOI: 10.1142/s1793604716500697
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of energy harvesting based on the uniform deformation of piezoelectric ceramic

Abstract: Since the piezoelectric properties were used for energy harvesting, almost all forms of energy harvester needs to be bonded with a mass block to achieve pre-stress. In this article, disc type piezoelectric energy harvester is chosen as the research object and the relationship between mass bonding area and power output is studied. It is found that if the bonding area is changed as curved, which is usually complanate in previous studies, the deformation of the circular piezoelectric ceramic is more uniform and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For instance, a pressure energy harvester made with prestressed piezoelectric discs has provided an output power density of >10 mW cm −3 which is the record for the energy harvesters made of piezoelectric ceramics, especially for conventional PZT . There are many publications available for the topic of prestressed piezoelectric energy harvesters …”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…For instance, a pressure energy harvester made with prestressed piezoelectric discs has provided an output power density of >10 mW cm −3 which is the record for the energy harvesters made of piezoelectric ceramics, especially for conventional PZT . There are many publications available for the topic of prestressed piezoelectric energy harvesters …”
Section: Development Of Single‐source Energy Harvestersmentioning
confidence: 99%
“…Most of the works with the title of optimisation with the aim of generating maximum possible power have not used optimisation algorithms to compromise between structural parameters but commonly have changed some parameters and have reached a larger power than before. Some of the attempts seeking the optimum structures are as follows: changing the radius of the annular electrodes of a circular piezoelectric [19], finding the best piezoelectric transducer length and cross-section independently [20], observing the variations of the structural parameters while keeping the resonance frequency constant [21], investigating the effect of the different substrate thicknesses [4], finding the best substrate to piezoelectric thickness ratio [22], discussing different length, width and thickness for triangular beam array [23] and installing the lead zirconate titanate (PZT) layers at the fixed, middle and free end of the substrate [24].…”
Section: Introductionmentioning
confidence: 99%
“…These were not the optimized results. Previous work [31,[41][42][43][44][45][46] has shown that potential improvement can be made. Here, however, the focus was on the demonstration of the add-on effects to be gained from multi-source energy conversion.…”
Section: Piezoelectric Effectmentioning
confidence: 99%